2014
DOI: 10.1051/0004-6361/201423531
|View full text |Cite
|
Sign up to set email alerts
|

Glory revealed in disk-integrated photometry of Venus

Abstract: Context. Reflected light from a spatially unresolved planet yields unique insight into the overall optical properties of the planet cover. Glories are optical phenomena caused by light that is backscattered within spherical droplets following a narrow distribution of sizes; they are well known on Earth as localised features above liquid clouds. Aims. Here we report the first evidence for a glory in the disk-integrated photometry of Venus and, in turn, of any planet. Methods. We used previously published phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Firstly, a glory feature in disk-integrated photometry data (Mallama et al, 2006), similar to our IR1 data, is identified by García Muñoz et al (2014). In this paper, we focused on Mallama et al's I-band data (the same wavelength with the IR1 data) but the glory in their data was more noticeable in shorter wavelengths (García Muñoz et al, 2014).…”
Section: Summary and Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Firstly, a glory feature in disk-integrated photometry data (Mallama et al, 2006), similar to our IR1 data, is identified by García Muñoz et al (2014). In this paper, we focused on Mallama et al's I-band data (the same wavelength with the IR1 data) but the glory in their data was more noticeable in shorter wavelengths (García Muñoz et al, 2014).…”
Section: Summary and Discussionsupporting
confidence: 50%
“…The agreement between the observed data and model computation is found to be fairly good, although there is substantial scattering in the observed data at small phase angles. The model curve indicates a shallow minimum around a $ 10°, which was identified as a glory feature in I band (García Muñoz et al, 2014).…”
Section: Standard Model Against Mallama Et Al's Curvementioning
confidence: 94%
“…Ground-based data as well as spacecraft observations (e.g., Venus Express, Voyager 1 and 2, Pioneer 10 and 11) have been used to investigate, e.g., Venus (e.g., Arking & Potter 1968;García Muñoz et al 2014;Petrova et al 2015), Titan (e.g., Rages et al 1983), Jupiter (e.g., Tomasko et al 1978;Smith & Tomasko 1984), Saturn (e.g., Tomasko & Doose 1984) or Uranus (Rages et al 1991;Pryor et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Spectral data were convolved using the filter transmittance function of the 365- nm channel of VMC, and we applied the same photometric correction as for the images. In order to take into account UVI's 2011 data, we calculated whole-disk albedo (Sromovsky et al 2001;García Muñoz et al 2014, 2017, without photometric correction due to the small apparent size of Venus (Section 3.2). Radiative transfer model calculations were performed using the model and gaseous database in Lee et al (2015bLee et al ( , 2016) (Section 3.3), to estimate the abundance of the unknown absorber that explains the observed 365-nm albedo, and to calculate solar heating rates.…”
Section: Methodsmentioning
confidence: 99%
“…r o is the radius range in which the measured radiance are summed considering the point spread function of the instrument (5 pixels) that is the required radius of aperture photometry of UVI star flux analysis. The whole-disk albedo can be expressed as A g Φ(α), where A g is geometric albedo, and Φ(α) is the phase law of Venus, describing the disk-integrated scattering efficiency as a function of phase angle (García Muñoz et al 2014, 2017.…”
Section: Whole-disk Albedomentioning
confidence: 99%